Tirzepatide: Does the Evidence to Date Show Potential for the Treatment of Early Stage Type 2 Diabetes? - Razzaki TS; Weiner A; Shukla AP (Dove Medical Press, 2022)
Tanzila S Razzaki,* Alyson Weiner,* Alpana P Shukla Comprehensive Weight Control Center, Division of Endocrinology, Diabetes, and Metabolism Weill Cornell Medicine, New York, NY, USA*These authors contributed equally to this workCorrespondence: Alpana P Shukla, Email aps2004@med.cornell.eduAbstract: Tirzepatide is a novel "twincretin" with glucagon-like peptide 1 and glucose-dependent insulinotropic polypeptide receptor agonist activity, which was recently approved by the Food and Drug Administration for the treatment of type 2 diabetes mellitus. In this review, we discuss preclinical and mechanistic human studies, which demonstrate improvements in insulin sensitivity and beta-cell function with the use of tirzepatide, as compared to placebo and glucagon-like peptide 1 receptor agonists. We then discuss SURPASS trials 1- 5, which evaluated the safety and efficacy of tirzepatide for type 2 diabetes mellitus as either monotherapy or combination therapy with other antidiabetic agents. The magnitude of tirzepatide's effects and the efficacy relative to other anti-diabetes medications on weight, glycemic control, and beta-cell function may prove beneficial for the treatment of early type 2 diabetes mellitus. Further studies, including data on cardiovascular outcomes and long-term safety, will continue to elucidate the role of tirzepatide in the treatment algorithm of type 2 diabetes mellitus.Keywords: tirzepatide, type 2 diabetes mellitus, obesity, SURPASS trials, glucagon-like peptide 1 receptor agonists, glucose-dependent insulinotropic polypeptide receptor agonist, "twincretin&#x201D